Adaptive fault-tolerant architecture and routing algorithm for reliable many-core 3D-NoC systems - Ben Ahmed, Akram; Ben Abdallah, Abderazek (Journal of parallel and distributed computing, 2016)
During the last few decades, Three-dimensional Network-on-Chips (3D-NoCs) have been showing their advantages against 2D-NoC architectures. This is thanks to the reduced average interconnect length and lower interconnect-power consumption inherited from Three-dimensional Integrated Circuits (3D-ICs). On the other hand, questions about their reliability is starting to arise. This issue is mainly caused by their complex nature where a single faulty transistor may cause intolerable performance degradation or even the entire system collapse. To ensure their correct functionality, 3D-NoC systems must be fault-tolerant to any short-term malfunction or permanent physical damage to ensure message delivery on time while minimizing the performance degradation as much as possible. In this paper, we present a fault-tolerant 3D-NoC architecture, called 3D-Fault-Tolerant-OASIS (3D-FTO).11This project is partially supported by Competitive research funding, Ref. P1-5, Fukushima, Japan. With the aid of a light-weight routing algorithm, 3D-FTO manages to avoid the system failure at the presence of a large number of transient, intermittent, and permanent faults. Moreover, the proposed architecture is leveraging on reconfigurable components to handle the fault occurrence in links, input-buffers, and crossbar, where the faults are more often to happen. The proposed 3D-FTO system is able to work around different kinds of faults ensuring graceful performance degradation while minimizing the additional hardware complexity and remaining power-efficient. •Adaptive fault-tolerant 3D-Network-on-Chip system architecture.•RAB mechanism for deadlock recovery and fault-tolerance in input-buffers.•Traffic-Prediction-Unit technique for congestion relief.•Bypass-Link-on-Demand to tackle fault-occurrence in the Crossbar.•Fault-tolerance and graceful performance degradation obtained at high fault-rates.